Sasi Sebagai Kearifan Lokal dalam Mencegah Menularnya Covid-19 Di Provinsi Maluku - La Ode Angga (PAMALI: Pattimura Magister Law Review, 2021)
Introduction: Sasi means the prohibition of taking natural resources on land or at sea, which is based on several important and basic arguments. The principle on which the Sasi law is based is actually the principle of sustainable natural resource management.Purposes of the Research: Know and analyze the role of sasi law as local wisdom in preventing the spread of Covid 19 in the Maluku Province. the formulation of Sasi's law in expanding its meaning and scope of implementation, so that the place is applied in preventing the spread of Covid 19 in Maluku Province.Methods of the Research: This research was conducted using a juridical empirical approach which is a descriptive study of qualitative analysis. The research seeks to describe the Role of Sasi Law as Local Wisdom in Preventing the Transmission of Covid 19 in Maluku Provision.Results of the Research: The Sasi Law which is owned by the Indigenous Maluku people, especially Southeast Maluku, of course the Sasi Law (Adat Hawear) in Southeast Maluku Regency can be applied in the prevention of Covid 19 in Southeast Maluku Regency by holding customary deliberations (which is followed by Adat leaders (adat leaders) The customary leaders (traditional leaders) held deliberations and formulated customary law norms as to what would be applied to preventing pollution from spreading Covid 19.